Green Generation: Building Environmentally Caring Characters Early Childhood Through Green School Programs - Fatnia Amanda; Sudaryanti Sudaryanti (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Environmental awareness in childhood is a fundamental aspect in developing awareness, responsibility, and sustainable habits towards environmental conservation from an early age. This study aims to test the effectiveness of the Green School program on the environmental awareness of children aged 5–6 years. This study used an ex post facto quantitative design with a sample of 142 children from kindergartens in Blang Mangat District, selected through a purposive sampling technique. The research instrument was validated through content validity and showed a high reliability coefficient of 0.892. Data were analyzed using an independent sample t-test to compare children's environmental awareness based on the duration of the Green School program. The analysis showed a significant difference in environmental awareness between children who participated in the Green School program for 5 years and 3 years (t(142) = 5.57; p < 0.001; Cohen's d = 0.932). These findings indicate that the Green School program effectively contributes to strengthening the environmental awareness of early childhood children and has important implications for the development of policies and practices for early childhood education oriented towards environmental sustainability.